Sporting activity in the process of building human consciousness: the physical education teacher in schools as mediator of this process. Issue 2 (2nd July 2016) - Viotto Filho, Irineu Aliprando Tuim
Abstract: As defined by cultural–historical theory (CHT), activity is a category that (1) generally orients human developmental processes and (2) specifically orients human consciousness. This research, which was carried out with students at an elementary school in Presidente Prudente, SP, involved two different sports (futsal and handball) and sought to create the conditions for the construction and development of the collective consciousness of the participants. This was done while maintaining an awareness of universal values such as solidarity and cooperation in the achievement of group goals. Data collection was carried out using systematic observations during activities oriented by members of the GEIPEEthc (the study group for Intervention and Research in Education and CHT) as part of a sports intervention project developed within a wider school programme. The data collected were analysed and organised from a socio-historical perspective, thus highlighting the transformation of the subjects' consciousness, and emphasising collective activity and the valourisation of sports as important to the process of human development.